Tingkat Kematangan Gonad Bulu Babi (Tripneustes Gratilla) di Pantai Ahmad Rhangmayang Kecamatan Mesjid Raya Kabupaten Aceh Besar - Riza Nasrullah; Widya Sari; Siska Mellisa (Jurnal Ilmiah Mahasiswa Kelautan Perikanan Unsyiah, 2018)
This study aimed to determine the gonads maturity level of sea urchins (Tripneustes gratilla) found on Ahmad Rhangmanyang Beach, Mesjid Raya District, Aceh Besar Regency. Sampling was carried out from November to December of 2016 with a sampling interval of once a week. The location of the research sampling was done on Ahmad Rhangmanyang Beach, Desa Lamreh, Mesjid Raya District, Aceh Besar Regency (5°36'40.31"N and 95°32'58.36"E). The research method used was the exploration method. The sampling of T. gratilla sea urchins was using transects methods. Each transect was made with a length of 25 m and a width of 10 m. The sea urchins’ masses were weighed and the diameters were measured, after that, they were dissected and the gonads were taken. Then the gonads were also weighed and the morphologies were observed. Dosage histological study of the gonads was made by using paraffin method and hematoxylin eosin staining. The measured parameters were the diameter of the shell, the Gonads Maturity Index (GI) and the Gonads Maturity Level, as well as environmental parameters such as temperature, pH, DO, and salinity of the water. The Gonads Maturity Level was determined based on an overview of the gonads histology. The data analysis was done descriptively; the results were presented in the form of images and tables. The diameter of Tripneustes gratilla was between 4.9 – 8.6 cm (49 mm – 86 mm). The lowest and highest Tripneustes gratilla Gonads Maturity Index (GI) was at week 7, with the lowest GI value of 0.19 % and highest IKG value 6.65 % of the total, with an average Tripneustes gratillaGI value of 2,452 %. There were gonads with Gonads Maturity Level I – IV, and only 40% of Tripneustes gratilla sea urchins individuals which had reached the ripe stage and were ready to spawn. There was a diversity of gonads maturity between the Tripneustes gratilla sea urchins individuals found each month.       Penelitian ini bertujuan untuk mengetahuitingkat kematangan gonad bulu babi (Tripneustes gratilla) di Pantai Ahmad Rhangmanyang, Kecamatan Mesjid Raya, Kab. Aceh Besar. Pengambilan sampel dilaksanakan dua bulan dari bulan November sampai bulan Desember 2016 dengan interval pengambilan sampel satu minggu sekali.Adapun lokasi pengambilan sampel penelitian tersebut di Pantai Ahmad Rhangmanyang, Desa Lamreh, Kecamatan Mesjid Raya, Aceh Besar (5°36'40.31"LU dan 95°32'58.36"BT).Metode penelitian yangdigunakan adalah metode eksplorasi.Pengambilan sampel bulu babi T. gratilla menggunakan metode transek.Setiap transek dibuat dengan ukuran panjang 25 m dan lebar 10 m. Bulu babi ditimbang bobot tubuh dan diukur diameternya, lalu dibedah dan diambil gonadnya.Gonad ditimbang dan diamati morfologinya.Sediaan histologis gonad dibuat dengan menggunakan metode parafin dan pewarnaan hematoksilin eosin. Parameter yang diukur adalah diameter cangkang tubuh, Indeks Kematangan Gonad (IKG), dan Tingkat Kematangan Gonad (TKG) serta parameter lingkungan seperti suhu, pH, DO dan salinitas air.TKG ditetapkan berdasarkan gambaran histologi gonad.Analisi data dilaksanakan secara deskriptif.Data hasil penelitian disajikan dalam bentuk gambar dan tabel.Diameter T. gratilla antara 4,9 – 8,6 cm (49 – 86 mm). IKG T. gratilla terendah dan tertinggi terdapat pada minggu  ke 7 yaitu dengan nilai IKG terendah sebesar 0,19 % dan IKG tertinggi sebesar 6,65 % dengan nilai rata - rata IKG sebesar 2,452 %. Ditemukan gonad dengan TKG I – IV  dan hanya 40% individu bulu babi T. gratilla yang telah mencapai matang goand dan siap memijah. terdapat keragaman kematangan gonad antar individu bulu babi T. gratillayang ditemukan pada setiap bulan.